2008
DOI: 10.1097/qad.0b013e3282fbd1c4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance impairs rapid virologic response in HIV/hepatitis C virus coinfected patients on peginterferon-alfa-2a

Abstract: The homeostasis model of assessment-insulin resistance score should be evaluated and possibly corrected before starting anti-hepatitis C virus therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
4
21
0
1
Order By: Relevance
“…This is the first study that has evaluated the relationships between IR and SVR in HIV/HCV co-infected patients. Nasta and coworkers [32] have suggested that IR may influence rapid virological response (RVR), defined as negative HCV PCR at week 4, in these subjects. In their analysis of 74 co-infected patients, RVR occurred in 27% and in 54% of those with a HOMA value above and below 3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study that has evaluated the relationships between IR and SVR in HIV/HCV co-infected patients. Nasta and coworkers [32] have suggested that IR may influence rapid virological response (RVR), defined as negative HCV PCR at week 4, in these subjects. In their analysis of 74 co-infected patients, RVR occurred in 27% and in 54% of those with a HOMA value above and below 3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of steatosis, apoptosis is correlated with activation of stellate cells and increased stage of fibrosis, in keeping with the hypothesis that a steatotic liver is more vulnerable to liver injury, and suggesting another mechanism of liver disease progression in patients with fatty liver and the metabolic syndrome [109] . Increasing levels of IR are associated with reduced rates of initial virological response [111][112][113] as well as SVR in chronic hepatitis C patients treated with a combination of pegylated IFN-a and ribavirin [114][115][116][117][118][119] . This negative association has been reported not only in patients infected with the HCV genotype 1 [114,116,119] , but also in those with the so-called "easy-to-treat" genotypes 2 and 3 [118] .…”
Section: Clinical Consequences Of Ir/t2d In Chronic Hepatitis Cmentioning
confidence: 99%
“…However, important and confounding interference of the protease inhibitor exposure on both viral load and insulin resistance has been hypothesized in these patients [18].…”
Section: Number Of Patientsmentioning
confidence: 99%